Horner's Syndrome as Initial Manifestation of Possible Brachial Plexopathy Neurolymphomatosis - Rai, Wijdan; Olcese, Vanessa; Elsheikh, Bakri; Stino, Amro Maher (Frontiers in Neurology, 2019)
Introduction: Horner’s syndrome is an established clinical finding unique to neoplastic brachial plexopathy. Background: We present the case of a patient who developed Horner’s syndrome as the first manifestation of neurolymphomatosis (NL) of the brachial plexus that did not have the usually associated bulky adenopathy / Pancoast syndrome phenotype. Discussion: We discuss the clinical utility of Horner’s syndrome with regards to brachial plexopathy of indeterminate etiology, as well as the utility of other diagnostic modalities in NL. Concluding remarks: NL, particularly of the brachial plexus, is particularly challenging to diagnose. MRI and CSF studies are often inconclusive. FDG-PET imaging can be difficult to get insurance to approve. The presence of Horner’s syndrome in brachial plexopathy of indeterminate etiology, even in the absence of bulky adenopathy, should raise clinical suspicion of NL, possibly prompting such interventions as fascicular nerve biopsy.